Datatype-generic termination proofs - Backhouse, Roland; Doornbos, Henk (Springer, 2008)
Datatype-generic programs are programs that are parameterised by a datatype. We review the allegorical foundations of a methodology of designing datatype-generic programs. The notion of F-reductivity, where F parametrises a datatype, is reviewed and a number of its properties are presented. The properties are used to give concise, effective proofs of termination of a number of datatype-generic programming schemas. The paper concludes with a concise proof of the well-foundedness of a datatype-generic occurs-in relation.